Effect of silver nitrate and growth regulators on direct shoot organogenesis and in vitro flowering from internodal segment explants of Alternanthera sessilis L. (November 2020) - Sowmya, M.; Jinu, U.; Sarathikannan, D; Geetha, N.; Girija, S.; Venkatachalam, P.
Abstract: The present report deciphers a rapid method for efficient shoot regeneration via direct organogenesis from internodal segment explants of Alternanthera sessilis. Internodal segment explants were placed on MS medium containing various doses of BAP and/or KIN (0.5–10.0 mg L ̶ 1 ) for shoot bud initiation. High frequency shoot bud induction (89%) was recorded on MS medium containing 2.5 mg L ̶ 1 BAP. Of the two cytokinin combinations tested, highest percent of plant regeneration (100%) with 81.1 shoots/culture was obtained on medium fortified with 2.5 mg L ̶ 1 BAP along with 50 mg L ̶ 1 adenine sulphate (AdS) and 0.5 mg L ̶ 1 silver nitrate (AgNO3 ) combination. Interestingly, BAP at 2.5 mg L ̶ 1 exhibited in vitro flowering from elongated shoots. Elongated shoot buds were carefully excised from the multiple shoot clumps and transferred onto half-strength MS medium without and/or fortified with different doses of NAA/IBA (0.1–1.0 mg L ̶ 1 ) for root initiation. IBA at 0.5 mg L ̶ 1 was found to be the best concentration for maximum percent of rooting (95.7%) over NAA. Well rooted plantlets were transferred into field conditions where they were successfully survived with 95%. It is noteworthy to mention that the random amplified polymorphic DNA (RAPD) and inter simple sequence repeat (ISSR) marker analysis between mother (control) and in vitro derived plantlets was found to be identical (monomorphic banding pattern) and no variability was observed with ISSR marker while RAPD marker showed 1.19% polymorphism. Hence, molecular results confirm that the in vitro regenerated plantlets were found to be the true-to-type in nature. In conclusion, the suitable growth hormonal combinations were identified for large scale production of genetically identical plantlets from internodal segment explants of Alternanthera sessilis . Highlights: High frequency plant regeneration via direct shoot organogenesis was achieved. Addition of silver nitrate and AdS exhibited multiple shoot bud development, elongation and in vitro flower formation. RAPD and ISSR markers confirmed the genetic fidelity of the regenerated plants.